Peran Guru PAI Dalam Menumbuhkan Kesadaran Spiritual Siswa Sebagai Benteng Terhadap Pengaruh Negatif Game Online di SMK Al-Azhar Batame di SMK AL-Azhar Batam - Mujrimin, Bayu; Supriadi, Supriadi (CV Najmi Edu Creative, 2025)
The increasing prevalence of online game addiction among students presents a significant threat to their spiritual development and character formation. This study aims to examine the role of Islamic Education (PAI) teachers in fostering students’ spiritual awareness as a preventive measure against the negative impact of online games. The research was conducted at SMK Al-Azhar Batam using a descriptive qualitative approach. Data were obtained through observation, interviews, and documentation involving 3 PAI teachers and 30 students. The findings reveal that PAI teachers play a strategic role in developing students’ spiritual awareness through the integration of Qur’anic values, modeling good behavior, and routine religious practices. These efforts help strengthen students’ self-control and resilience against the temptation of online games. The study concludes that spiritual education delivered by PAI teachers effectively contributes to shaping students’ positive behavior and serves as a strong protective factor against digital distractions, particularly excessive gaming.